PERANCANGAN MEJA KERJA DENGAN WOOD SLAT LAMINATED DI STUDIO DESAIN QUILIMO (Science and Technology (SciTech), 2022)
At present, the demands for jobs in graphic design companies have begun to expand, so many design industries require facilities or workplaces, one of which is a work desk. it is a mandatory product for working tools in graphic design companies or others. The design of this work desk uses the design thinking method as the main reference in m designing. The author makes research in a graphic design industri, namely in the quilimo studio, Quilimo is a brand name in the graphic design field that has 4-5 employees, this industri is a home-based company located in Sekuro Village. This study uses a qualitative method by collecting interview data, observations in the studio, followed by documentation in order to find out the problems that exist in the quilimo studio. After doing research at the Quilimo studio and collecting data, the problem at this design company is in the work desk that lacks ergonomics, one of which is the size of the table that is too narrow and not neat. The design of the work table with Wood Slat Laminated uses wood waste material because wood waste in the author's environment is very abundant and rarely used and utilized as a product that has a selling value. This workbench will be displayed in the graphic design studio room and become a solution to problems in the Quilimo design studio.